2010
DOI: 10.1080/13554790903456191
|View full text |Cite
|
Sign up to set email alerts
|

A case of post-traumatic complex auditory hallucinosis treated with rTMS

Abstract: Previous studies of auditory hallucinations in schizophrenia found that the hallucinations were reduced by the application of transcranial magnetic stimulation (rTMS). Here we describe a case of traumatic brain injury associated with continuous music hallucinations. An MRI scan showed a structural lesion of the right temporal pole and a PET scan indicated a hyperactive area of the posterior right temporal lobe. We hypothesized that rTMS applied to the right temporal area would reduce this activity and the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The MH disappeared after 2 weeks, only to reappear after 4 months; although by that time they were less intense, and only present in a quiet environment and before falling asleep (Cosentino et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MH disappeared after 2 weeks, only to reappear after 4 months; although by that time they were less intense, and only present in a quiet environment and before falling asleep (Cosentino et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…It tends to consist of antiepileptics, antidepressants, antipsychotics or acetylcholinesterase inhibitors, but even when treated for a sufficient amount of time and at adequate plasma levels, MH can be refractory to most of these treatments (Sacks and Blom, 2012). Repetitive transcranial magnetic stimulation (rTMS) may perhaps be a viable option in the near future, but so far it only showed a favorable response in a single medication-resistant patient with post-traumatic damage to the right temporal lobe (Cosentino et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, García-Toro et al reported clinical benefit of transcranial magnetic stimulation (rTMS) for patients with auditory hallucinations and tinnitus 57 and Cosentino et al reported one case of post-traumatic complex auditory hallucination treated with rTMS 58 .…”
Section: Treatmentmentioning
confidence: 99%
“…15 Stimulation parameters in this case were 110% of MT using 20 Hz and train duration of 2 seconds. In contrast, 2 recent case reports reported good tolerability of rTMS in patients with depression 18 and auditory hallucinations 19 after TBI. A recent review pointed out the promising potential of rTMS as a diagnostic and therapeutic tool, which should further be evaluated in TBI patients.…”
Section: Tms and Seizure Risk In Tbi Patientsmentioning
confidence: 86%
“…Also in TBIassociated depression 18 and hallucinations, 19 relatively pronounced clinical effects have been reported. These promising results, however, may be confounded by reporting bias because all data arise from case reports.…”
Section: Efficacy Of Rtms In Tbi Patientsmentioning
confidence: 98%